Britain, Europe and National Identity Self and Other in International Relations - Gibbins, Justin; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This study patterns national identity over a number of important historical milestones and brings the debates over Europe up-to-date with an analysis of recent happenings including the referendum on Scottish independence, the global economic crisis and the current crisis in Syria.
Keywords: Science; Science; Science, general